2011
DOI: 10.1021/jp2012254
|View full text |Cite
|
Sign up to set email alerts
|

Polarity, Viscosity, and Ionic Conductivity of Liquid Mixtures Containing [C4C1im][Ntf2] and a Molecular Component

Abstract: In this study, we have focused on binary mixtures composed of 1-butyl-3-methylimidazolium bis(trifluoromethanesulfonyl)-imide, [C(4)C(1)im][Ntf(2)], and a selection of six molecular components (acetonitrile, dichloromethane, methanol, 1-butanol, t-butanol, and water) varying in polarity, size, and isomerism. Two Kamlet-Taft parameters, the polarizability π* and the hydrogen bond acceptor β coefficient were determined by spectroscopic measurements. In most cases, the solvent power (dipolarity/polarizability) of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
62
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 155 publications
(65 citation statements)
references
References 40 publications
3
62
0
Order By: Relevance
“…where, * ,i P C is the isobaric molar heat capacity and listed in Table 7 As explained earlier by C. Lopez [27], the logarithm of viscosity of studied binary mixtures was given by Grunberg-Nissan equation [60]:…”
Section: Tablesmentioning
confidence: 99%
“…where, * ,i P C is the isobaric molar heat capacity and listed in Table 7 As explained earlier by C. Lopez [27], the logarithm of viscosity of studied binary mixtures was given by Grunberg-Nissan equation [60]:…”
Section: Tablesmentioning
confidence: 99%
“…This includes the relative strength and extensiveness of hydrogen bond networks and the relative abundance of H + /OH − among others available in the respective solvents. Studies of this nature have been carried out using binary mixtures of ionic liquids, and mixtures of water and ionic liquids and mixtures of molecular solvent and ionic liquid . The properties of whose variations are frequently studied upon mixing include density, viscosity and conductivity among others.…”
Section: Introductionmentioning
confidence: 99%
“…Molecular dynamics studies [35][36][37] have indicated that there is significant ionic association in neat ILs which leads to high viscosity, limited conductivity and other peculiar properties of these organic salts. Mixing ionic liquids with molecular solvents will reduce coulombic interactions and release free ions from their associations, leading to decreased viscosity and increased conductivity [13,38]. A fluid with a large dielectric constant (as is DMSO or ACN) can interact more effectively with both ions of the ionic liquid, disrupting its polar network and causing a decrease in the viscosity of the mixture.…”
Section: Resultsmentioning
confidence: 99%
“…A fluid with a large dielectric constant (as is DMSO or ACN) can interact more effectively with both ions of the ionic liquid, disrupting its polar network and causing a decrease in the viscosity of the mixture. As a result, it increases the conductivity, thus facilitating mass transport [14,38].…”
Section: Resultsmentioning
confidence: 99%